High-Intensity Interval Training as a Tool for Counteracting Dyslipidemia in Women - Alvarez, Cristian; Ramirez-Campillo, Rodrigo; Martinez-Salazar, Cristian; Castillo, Angélica; Gallardo, Francisco; Ciolac, Emmanuel Gomes [UNESP] (Thieme, 2018)
Sedentary overweight or obese adult (age<60 years) women, allocated in type 2 diabetes mellitus (T2DM, n =13), dyslipidemia alone (DYS, n =12), dyslipidemia associated with hyperglycaemia (DYSHG, N=12), or healthy control (CON, n =10) groups, had their lipid, glucose, blood pressure, endurance performance, and anthropometry variables assessed before and after 16 weeks of a thrice-weekly high-intensity interval training (HIIT) program. Triglycerides reduced significantly (P <0.05) in all groups, and high-density lipoprotein increased (P <0.01) in T2DM, DYS and DYSHG; however, low-density lipoprotein reduced (P <0.05) only in DYSHG, and total cholesterol reduced (P <0.01) only in DYS and DYSHG. Fasting glucose reduced (P <0.05) significantly in T2DM, DYS and DYSHG, but with higher decreases in T2DM and DYSHG. Blood pressure, endurance performance and body composition improved (P <0.05) in all groups. The HIIT program was effective for restoring lipid profile of DYS and DYSHG, and fasting glucose of DYSHG to levels similar to those of CON, with a weekly time commitment 25% to 56% lower than the minimum recommended in current exercise guidelines. These findings suggest that HIIT may be a time-efficient intervention for counteracting dyslipidemia.
Keywords: cardiometabolic alterations; co-morbidities; high-intensity interval exercise; lipoproteins; type 2 diabetes mellitus